Wiley's remediation technologies handbook : major contaminant chemicals and chemical groups - Lehr, Jay H., 1936- (Wiley-Interscience, 2004)
Wiley's Remediation Technologies Handbook: Major Contaminant Chemicals and Chemical Groups, extracted from the Enviroglobe database, consists of 368 chemicals and chemical groups. This book lists in alphabetical order these chemical and chemical groups along with the numerous technologies, many of which are patented, or trademarked techniques, to remediate them. A short description of each of these technologies is provided along with appropriate references.